Migrationsschule - Ströhle, Claudius (Bricolage monografien, 2017)
"At school, not only arithmetic and writing is taught. Pupils also learn to behave male or female, which means to be poor or rich - and to distinguish who is considered ""foreigner"" and who is not. In order to understand the significance of migration and ethnicity in everyday school life, the author accompanied and observed teachers and pupils at a new middle school in Tyrol. The resulting observation protocols, questionnaires and interviews are presented and analyzed in this ethnographic work. In this way, the readers are given a multi-layered insight into the school life from a migration perspective. It becomes clear that as a central institution of society, the school plays a decisive role in the mediation of images of others and of oneself."